Tax Principles and Tax Harmonization under Imperfect Competition: A Cautionary Example - Michael Keen; Sajal Lahiri; Pascalis Raimondos-Møller (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper shows that under imperfect competition the welfare effects of indirect tax harmonization may depend crucially on whether taxes are levied by the destination or the origin principle. In a standard model of imperfect competition, while harmonization always makes at least one country better off, and may be Pareto-improving, when taxes are levied under the destination principle (which currently applies in the European Union), harmonization of origin-based taxes (as recently proposed by the European Commission) is certain to be Pareto-worsening when the preferences in the two countries are identical, and is likely to be so even when they differ.
Keywords: 330; Harmonization; destination principle; origin principle; commodity taxation